2018
DOI: 10.3390/su10103537
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Professional Performance Evaluation System for Pre-Service Automobile Repair Vocational High School Teachers in Taiwan

Abstract: Educational quality is one of the most important factors for having well-trained human resources that support the productivity, competitiveness, and economic growth of a nation. Teachers have always played dominant roles in ensuring education quality. Thus, teacher education is becoming ever more important. However, scholars have long warned about the ineffectiveness of teacher preparation. Indeed, a significant gap still exists between current pre-service teacher education and ideal training. Thus, a new prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Wu et al reported "Developing a Professional Performance Evaluation System for Pre-Service Automobile Repair Vocational High School Teachers in Taiwan" [31]. In this study, developing a performance evaluation system that contains professional standards, performance evaluation criteria, and a precise performance evaluation mechanism are seen as essential to guarantee the highest teacher quality in Taiwan.…”
Section: Tu Et Al Reported "Key Factors Of Sustainability For Smartpmentioning
confidence: 92%
“…Wu et al reported "Developing a Professional Performance Evaluation System for Pre-Service Automobile Repair Vocational High School Teachers in Taiwan" [31]. In this study, developing a performance evaluation system that contains professional standards, performance evaluation criteria, and a precise performance evaluation mechanism are seen as essential to guarantee the highest teacher quality in Taiwan.…”
Section: Tu Et Al Reported "Key Factors Of Sustainability For Smartpmentioning
confidence: 92%
“…For example, Huang et al [53] proposed a multiple objective programming-based DEA model for evaluating the performance of leading fabless integrated-circuit design houses. Wu et al [54] developed a professional performance evaluation system for pre-service automobile repair vocational high-school teachers in Taiwan. Han and Trimi [55] proposed a fuzzy technique for order preference according to its similarity to the ideal solution (TOPSIS) method.…”
Section: Performance Evaluation Of the Iacmentioning
confidence: 99%
“…Management work is very much done by the teacher in performing the responsibilities and is a priority in assessing the performance of the teacher through each activity and program. According to Wu, Huang, Kao, Lue and Chen (2018), teacher competence can be assessed through teaching skills, classroom management skills or workshops, involvement in student counseling and referrals, student family relationships, good relationship with the administration, personal characteristics, as well as professionalism. This means that management competency is very much needed by the teacher, where the assessment of one's level of competence can be demonstrated through the way the teacher deals with matters and it can be improved through experience.…”
Section: The Needs Of Management Competency For Tvet's Teachersmentioning
confidence: 99%